Circulating TNF and mitochondrial DNA are major determinants of neutrophil phenotype in the advanced-age, frail elderly. Issue 1 (May 2015) - Verschoor, Chris P.; Loukov, Dessi; Naidoo, Avee; Puchta, Alicja; Johnstone, Jennie; Millar, Jamie; Lelic, Alina; Novakowski, Kyle E.; Dorrington, Michael G.; Loeb, Mark; Bramson, Jonathan L.; Bowdish, Dawn M.E.
Highlights Blood neutrophils appear basally activated and are immature in the advanced-age, frail elderly. CD11b and HLA-DR expression is related to the levels of circulating TNF and mtDNA in humans. Loss of TNF in mice abrogates age-related increases in neutrophil CD11b in vivo. mtDNA is able to induce neutrophil HLA-DR in a dose-dependent fashion ex vivo.